Prostitution: sex work, policy and politics - Sanders, Teela (SAGE, 2009)
This is the first textbook to offer a complete overview of the way prostitution operates within contemporary society, its characteristics, organizational structures and cultural contexts. The book also explores how criminal and social policies have sought to regulate and control the selling of sex.